A historical approach by the authors Lactantius and Augustinus through their books "The Divine Systems" and "The City of God" - Abdel Nour, Omari (The Algerian Historical Journal, 2026)
The history of the ancient Maghreb is full of scientific, religious and literary figures that had a great influence on human thought, and most of them were written in Latin. Among these are two mystical thinkers and researchers of Christian theology of Afro-Maghreb origin, Lactantius Caecilius Firminus, who is best known for his famous author of the Christian world, The Encyclopedia of "Divine Systems", which had a great influence on medieval and later Renaissance thought. Also, the book "The City of God" by St. Augustine, this book had a great influence on Christian thought and culture. In this work, I will try to present a historical approach to both authors and to know the positives and shortcomings that these works carry to achieve their goals